The relationship of personal resources and types of professional careers of doctors - V. V. Mathan (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
The article describes the personal resources of doctors associated with their professional success. The study involved 123 doctors of city hospitals in St. Petersburg. Based on a factor analysis, five types of career were identified; two of them were classified as successful, two as unsuccessful and one as neutral. Significant correlations were found between personal resources and three types of career. In order to explain the nature of these relationships, as well as the search for the reasons for the lack of significant correlations of personal resources and two other types of career, further research is needed.